Management of Agricultural Machinery - Ibrahim, Fauzi; Apriyanto, Agus; Murti, Adam Wisnu; Putri, Novia Utami (Fakultas Teknik Universitas Malahayati, 2025)
The integration of intelligent machinery and autonomous vehicles into agricultural operations offers opportunities for enhanced efficiency and reduced environmental impact. Innovations in sensing, actuation, and information and communication technologies (ICT) present significant potential for advancing agricultural practices. However, fully leveraging these advancements requires revisiting traditional agricultural machinery management processes. Conventional planning methodologies, such as job-shop scheduling, must be augmented with modern approaches like route optimization and sequential task scheduling. This review highlights current advancements and future needs in agricultural machinery management, focusing on five key management tasks across strategic, tactical, operational, and evaluative levels. The study identifies the importance of integrating these tasks with advanced tools and models to enable efficient and sustainable agricultural operations. Future directions emphasize adaptive planning, real-time decision-making, and enhanced system integration to address location-specific and environmental challenges.